2021
DOI: 10.18844/jeset.v7i1.6793
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion at the University through technology: A case study in Italy

Abstract: During the pandemic, it was important to recognize the need of involving students in the process of understanding and improving their academic experience. This study aimed to investigate whether or not the online learning environment provided by the university was accessible and which teaching strategies were most conducive to learning. Data were collected through a survey, of which 116 university students with disabilities and SpLDs took part in; 78 were female (67.2%) and 38 were male. Specifically, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…To cope with traumatic experiences of being in isolation, the study revealed that participants employed active coping strategies which included engaging in online games at home, exercising, turning to prayer, and also confronting the virus by talking to the virus as something that has ears Bianco et al, 2021;Gipal et al, 2022). The study could not isolate any passive coping strategies from the Survivors of Covid-19.…”
Section: Discussionmentioning
confidence: 97%
“…To cope with traumatic experiences of being in isolation, the study revealed that participants employed active coping strategies which included engaging in online games at home, exercising, turning to prayer, and also confronting the virus by talking to the virus as something that has ears Bianco et al, 2021;Gipal et al, 2022). The study could not isolate any passive coping strategies from the Survivors of Covid-19.…”
Section: Discussionmentioning
confidence: 97%
“…They also help the translator to manage visual content, such as page layout and design, to be ready for publication. Thus, such applications need to be taken into careful attention not only by translation students but also by expert translators if they want to increase their productivity and reduce translation costs (Bianco et al, 2021;Markoska, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, conceptualisations of digital competence are associated with many features such as information, media and communication studies, education and information sciences/systems (Elmira et al, 2022;Murawski & Bick, 2017;Oberlander, Beinicke, & Bipp, 2020). Digital competence is all the knowledge, skills and attitudes that an individual employs in the process of accessing, understanding and using information in different formats in various digital environments (Bianco, Giaconi, Gison, D'Angelo, & Capellini, 2021). With the increase in online learning opportunities, digital competencies are among the prominent concepts recently and among the most important skills specified by experts in the fields of policy, education and science (Alamer et al, 2022).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%